Translocation of mercury from substrate to fruit bodies of Panellus stipticus, Psilocybe cubensis, Schizophyllum commune and Stropharia rugosoannulata on oat flakes - Gabriel, Jiří; Švec, Karel; Kolihová, Dana; Tlustoš, Pavel; Száková, Jiřina (Ecotoxicology and environmental safety, 2016)
The cultivation and fructification of 15 saprotrophic and wood-rotting fungal strains were tested on three various semi-natural medium. The formation of fruit bodies was observed for Panellus stipticus, Psilocybe cubensis, Schizophyllum commune and Stropharia rugosoannulata in the frame of 1-2 months. Mercury translocation from the substrate to the fruit bodies was then followed in oat flakes medium. Translocation was followed for treatments of 0, 1.25, 2.5, 5, 10 and 20ppm Hg in the substrate. All four fungi formed fruit bodies in almost all replicates. The fruit body yield varied from 0.5 to 15.3g dry weight. The highest bioconcentration factor (BCF) of 2.99 was found for P. cubensis at 1.25ppm Hg. The BCF decreased with increasing Hg concentration in the substrate: 2.49, 0, 2.38, 1.71 and 1.82 for P. stipticus; 3.00, 2.78, 2.48, 1.81 and 2.15 for P. cubensis; 2.47, 1.81, 1.78, 1.07 and 0.96 for S. commune; and 1.96, 1.84, 1.21, 1.71 and 0.96 for S. rugosoannulata. The Hg contents in the fruit bodies reflected the Hg contents in the substrate; the highest contents in the fruit bodies were found in P. cubensis (43.08±7.36ppm Hg) and P. stipticus (36.42±3.39ppm).
Keywords: oves; Fructification; rtuť; Fungi; Psilocybe; Translocation; Agaricales; Culture Media; Mercury; Fruiting Bodies, Fungal; Schizophyllum; plodnice hub; Avena; kultivační média; Bioaccumulation